Assessment of imidacloprid related exposure using imidacloprid-olefin and desnitro-imidacloprid: Neonicotinoid insecticides in human urine in Wuhan, China. (August 2020) - Wang, Aizhen; Mahai, Gaga; Wan, Yanjian; Yang, Zong; He, Zhenyu; Xu, Shunqing; Xia, Wei
Graphical abstract: Highlights: DN-IMI, IMI-olefin, and DM-ACE had high detection frequencies. Fair-to-good inter-day reliability was found for DN-IMI, IMI-olefin, and DM-ACE. DN-IMI and IMI-olefin were identified in human urine for the first time. Higher urinary NNI concentrations were found in urban areas and in autumn. Abstract: While neonicotinoid insecticides (NNIs) have been widely used worldwide, limited studies have measured specific metabolites of imidacloprid (IMI, the most commonly used NNI) in human urine. To better understand human exposure to NNIs, 10 parent compounds, and 6 of their metabolites were analyzed in 408 urine samples collected from 129 healthy adults in Wuhan, Central China, during autumn and winter of 2018. These specimens included repeated urine samples taken in 3 d from 75 volunteers. The urinary concentrations of desnitro-imidacloprid (DN-IMI), imidacloprid-olefin (IMI-olefin), and desmethyl-acetamiprid (DM-ACE) were higher (4–40 times) than those of their parent compounds (IMI and acetamiprid, ACE). DN-IMI and IMI-olefin accounted for 92% of the urinary Σ3 IMI (the sum of IMI and its specific metabolites measured). Positive correlations ( r ) were observed between DN-IMI and IMI (0.50), IMI-olefin and IMI (0.75), and DM-ACE and ACE (0.53). Good to excellent inter-day reliabilities (unadjusted intraclass correlation coefficients) were observed for IMI-olefin (0.61) and DM-ACE (0.81), while moderate inter-day reliability was observed for DN-IMI (0.43). The urinary NNI concentrations were significantly higher in autumn than in winter, and higher in urban areas than in rural areas, while no significant gender or age-related differences were observed. To our knowledge, this is the first report on DN-IMI and IMI-olefin in human urine.